2021
DOI: 10.1002/jms.4725
|View full text |Cite
|
Sign up to set email alerts
|

Cold‐spray ionization mass spectrometry of the choline chloride‐urea deep eutectic solvent (reline)

Abstract: Cold‐Spray Ionization mass spectrometry (CSI‐MS) that can be compared to an electrospray ionization (ESI) source acting with a nebulizing gas cooled by liquid nitrogen is used for analyzing reline as Deep Eutectic Solvent (DES). The association of cholinium chloride salts with urea molecules is evidenced in negative CSI‐MS through the chloride adduct formation. The structure of the supramolecular assemblies forming the reline ions that are observed on CSI mass spectra is rationalized by chemical quantum calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…CSI MS used it to analyze reline, i.e., Choline chloride: urea (1:2, mol/mol). [26] The ions detected on the CSI MS were distinctive of Choline Chloride salt and Urea association into a chloride adduct. It was found that an increase in the number of urea molecules does not imply a stabilization of the NaDES.…”
Section: Mass Spectrometrymentioning
confidence: 97%
See 1 more Smart Citation
“…CSI MS used it to analyze reline, i.e., Choline chloride: urea (1:2, mol/mol). [26] The ions detected on the CSI MS were distinctive of Choline Chloride salt and Urea association into a chloride adduct. It was found that an increase in the number of urea molecules does not imply a stabilization of the NaDES.…”
Section: Mass Spectrometrymentioning
confidence: 97%
“…Indeed, classical assay based on colorimetric measurement could be disturbed by the NaDES component leading to intensive research of alternative processes. For example, the direct electrochemistry of nine phenolic compounds was investigated for the first time in three DES-based media by cyclic voltammetry and differential pulse voltammetry in comparison with the Folin-Ciocalteu assay by Percevault et al [26]. The Folin-Ciocalteu test is routinely employed for determining the total phenolic content in extracts; even though it is widely used in DES extracts [47], sometimes it can be difficult to handle or even inaccurate in some (Na)DES, while electrochemical techniques are quick, simple and do not require the use of metals or organic reagents.…”
Section: Post-extraction Step 61 Biological Evaluationmentioning
confidence: 99%
“…This led to a supramolecular network made by the association of one cholinium chloride salt and two urea molecules. 27,[29][30][31][32]…”
Section: Des Preparationmentioning
confidence: 99%
“…[21][22][23][24][25][26] Their organization can be described through non-covalent molecular networks associating a hydrogen bond acceptor (HBA) and a hydrogen bond donor (HBD). [27][28][29][30][31][32] Examples of DES applications in chemistry were described through extraction and microextraction techniques, [33][34][35][36] electrochemistry, 37 and catalysis. 38,39 Several studies have also shown that DESs based on choline chloride were able to absorb air contaminants such as sulfur dioxide 40,41 or ammonia.…”
Section: Introductionmentioning
confidence: 99%